Comprehensive the effects of Counseling grouping with Gestalt therapy approach and Reality therapy on Emotion Regulation in adolescent girls - Rousta, Negar; Ghadami, Majid; Keshavarz Afshar, Hossein; Ahghar, Ghodsi (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The effectiveness of group counseling was compared with Gestalt therapy and reality therapy on emotional regulation of adolescent girls in Tehran. Methods: The current research was a semi-experimental type with a pre-test-post-test design with a control group and a follow-up phase. The statistical population included all teenage girls in the first year of high school in public schools in Tehran in the academic year 2018-2019. 45 people were selected using the purposeful sampling method and were randomly divided into three groups of 15 people. . The first experimental group received 10 90-minute sessions of group counseling with the Gestalt therapy approach, and the second experimental group received 10 90-minute sessions of reality therapy counseling. The research tool was the emotion regulation questionnaire of Garnevsky and Karij (2006). The data were analyzed using the method of variance analysis of repeated measures. Results: The results showed that Gestalt therapy intervention (F = 5.88, P = 0.020) and Reality therapy intervention (F = 5.77, P = 0.023) were effective on the emotional regulation score, and this effect was stable in the follow-up phase. Conclusion: Gestalt therapy group counseling and reality therapy have had a positive and significant effect on emotion regulation; therefore, group counseling, methodical Gestalt therapy and reality therapy are suitable methods to increase emotional regulation of teenagers. According to the obtained results, it is suggested that school counselors and psychotherapy centers use group counseling methods with Gestalt therapy and reality therapy to improve emotion regulation.